Introduction - Flüchter, Antje; Schöttli, Jivanta (The dynamics of transculturality, 2015)
The overarching theme for the 2010 Annual Conference of the Cluster, Asia and Europe in a Global Context was dynamics of transculturality and the processes of transculturalisation through concepts and institutions in the field of politics and religion. In the last decade, transculturality has become an oft--perhaps too-often--used term, and has in the process arguably lost some of its heuristic value. This edited volume begins with a more precise concept of transculturality, but it also mirrors the discussions about transculturality and asymmetric flows that have taken place in the first 5 years of the Cluster. As a starting point, this introduction will examine the notion of transculturality as a theoretical perspective and heuristic instrument, it will then move on to present the main focus of this volume: the dynamics of transculturality in the realms of politics and religion. The third part of this introduction will consider a number of concepts that are available to a transcultural perspective and discuss those employed by the authors in this book.